Implementation of a Web-based Income Statement Accounting Information System: a Case Study at Toko Amanah Kepanjen, Malang Regency - Kusmintarti, Anik; Ekasari, Kurnia; Kinasih, Asti Sekar (Formosa Journal of Science and Technology, 2024)
The aim of this research is to determine the efficiency and effectiveness after implementing an accounting information system for income statements at Toko Amanah. This study uses applied research with a Research & Development (R&D) method and employs the ADDIE approach, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection was carried out through observation and interviews with research subjects, as well as questionnaires for application testing. The result of this research is a website that includes sales, inventory, and income statement reports, which were previously managed manually. The implementation of a web-based accounting information system has proven to enhance the effectiveness and efficiency of the subject, as well as improve the accuracy of the reports generated. After the system design has been completed, the system is tested by users, IT experts, and subject matter experts.